Subject-Object Positions in Women's Reporting: A Study of Gender Bias in iNews.com Online Media - Rahmadina Riftia Novianti; Fafi Inayatillah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the position of subject-object participants in women’s news coverage on iNews.com using Sara Mills’ Critical Discourse Analysis feminist stylistic model. This study uses a qualitative approach with a descriptive research type. The data sources are five iNews.com news texts published in the period June–October 2025. The research data are in the form of words, phrases/sentences, and paragraphs containing gender bias. The data collection technique is carried out through reading and note-taking techniques. At this stage, it is done by carefully reading the news from the iNews.com portal for the period June–October 2025 that presents women as the main subject or object and contains issues of gender and gender-based violence. After reading, the process of recording the data obtained is required. Data analysis is carried out through the stages of data reduction, coding, analysis, presentation, and drawing conclusions based on Sara Mills’ analysis categories, namely the position of subject-object participants. The data validity technique uses a credibility test through extended observation, increased persistence, and discussions with linguistic researchers. The research results show that reporting about women on iNews.com contains gender bias, characterized by the dominance of women as passive and stereotypical news objects, the use of subordinating diction, and power relations that marginalize women. This indicates that reporting practices on iNews.com are not fully gender-sensitive and continue to reproduce gender inequality in media discourse.